2019
DOI: 10.3390/en12040758
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Cooling Effect of Attached Fins on PV Using CFD Simulation

Abstract: The issue of efficiency decrease according to temperature increase is a pending problem in the PV market. Several active and passive technologies have been suggested but few quantitative studies on the estimation of the cooling effect have been carried out. In this study, a CFD (computational fluid dynamics) simulation model was developed to analyze a passive cooling technology using fins attached to the back of the PV module. Furthermore, a method to improve airflow at the back of the PV module by forming sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Then, water is used to cool the PCM, which ejects heat into the environment. This last method of cooling PV modules is an important research topic (see, e.g., [44]) together with systems that add thins to the module [45].…”
mentioning
confidence: 99%
“…Then, water is used to cool the PCM, which ejects heat into the environment. This last method of cooling PV modules is an important research topic (see, e.g., [44]) together with systems that add thins to the module [45].…”
mentioning
confidence: 99%
“…In this study, it can be concluded that the higher the number of fins, the higher the rate of heat transfer of the solar cell. Jaemin Kim & Yujin Nam [4] analysed a study on the cooling effect of attached fins on PV using CFD simulation. The results of the CFD simulation show that the installation of the fins influenced the airflow and temperature distribution at the bottom of the PV module, where the temperature difference was reduced to less than 4.6 °C when the fins were mounted.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, active and passive cooling systems [7] are adopted to reduce PV cell temperature, and several designs have been proposed in literature [8][9][10][11][12][13][14][15]. The main advantage of active cooling systems is a more efficient heat removal rate; for this reason, they are generally preferred to passive systems, in which a cooling fluid circulates without needing additional power.…”
Section: Introductionmentioning
confidence: 99%